If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 2x = 19 + 3x Solving -11 + 2x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -11 + 2x + -3x = 19 + 3x + -3x Combine like terms: 2x + -3x = -1x -11 + -1x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 -11 + -1x = 19 + 0 -11 + -1x = 19 Add '11' to each side of the equation. -11 + 11 + -1x = 19 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 19 + 11 -1x = 19 + 11 Combine like terms: 19 + 11 = 30 -1x = 30 Divide each side by '-1'. x = -30 Simplifying x = -30
| 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 |